The Origin of Social Evaluation, Social Eavesdropping, Reputation Formation, Image Scoring or What You Will - Abdai, Judit; Miklósi, Ádám (Frontiers in Psychology, 2016)
Social evaluation is a mental process that leverages the preference toward prosocial partners (positivity bias) against the avoidance of antisocial individuals (negativity bias) in a cooperative context. The phenomenon is well-known in humans, and recently comparative investigations looked at the possible evolutionary origins. So far social evaluation has been investigated mainly in non-human and human primates and dogs, however, there are few data on the presence of negativity/positivity bias in client-cleaner reef fish interactions as well. Unfortunately, the comparative approach to social evaluation is hindered by conceptual and procedural differences in experimental studies. By reviewing current knowledge on social evaluation in different species, we aim to point out that the capacity for social evaluation is not restricted to humans alone; however, its building blocks (negativity and positivity bias) may be more widespread separately. Due to its importance in survival, negativity bias likely to be widespread among animals; however, there has been less intensive selective pressure for the identification of prosocial companions, thus the latter ability may have emerged only in certain social species. We present a general framework and argue that negativity and positivity bias evolve independently and can be considered as social evaluation only if a unified behavior and cognitive system deals with both biases in concert.